Waste excretion of marble goby (Oxyeleotris marmorata bleeker) - Lam, Su Shiung (Institut Akuakultur Tropika, 2011)
Marble goby (Oxyeleotris marmorata Bleeker), a freshwater food fish with its high demand and price, has a great potential as a profitable commercial aquaculture candidate in Malaysia and Southeast Asia region. With respect to their good prospect, this study was conducted to collect growth and waste excretion data that would be of value for the design and management of a more effective recirculating aquaculture system (RAS) for growout production of this fish due to poor growth performance and disease problems shown by conventional cage and pond culture systems.